Use of computer-assisted detection (CADe) colonoscopy in colorectal cancer screening and surveillance: European Society of Gastrointestinal Endoscopy (ESGE) Position Statement - Bretthauer, Michael; Ahmed, Jabed; Antonelli, Giulio; Beaumont, Hanneke; Beg, Sabina; Benson, Ariel; Bisschops, Raf; De Cristofaro, Elena; Gibbons, Eimear; Häfner, Michael; Karsenti, David; Laquière, Arthur; Loly, Jean-Philippe; O’Reilly, Susanne M.; Pellisé, Maria; Grubelic Ravic, Katja; Triantafyllou, Konstantinos; Tziatzios, Georgios; Valente, Roberto; Walter, Benjamin M.; Wiesand, Malina; Lorenzo-Zúñiga, Vicente; Gralnek, Ian Mark (Endoscopy, 2025)
This statement conveys the European Society of Gastrointestinal Endoscopy (ESGE) position on the use of computer-aided detection (CADe) with artificial intelligence (AI) during colonoscopy for colorectal cancer (CRC) screening or surveillance. The ESGE position is informed by the BMJ Rapid Recommendation initiative and the approach of the MAGIC Evidence Ecosystem Foundation; these include systematic reviews of currently available evidence, supplemented by microsimulation modeling and patient values and preferences, for the benefits and harms of AI CADe devices during colonoscopy.ESGE convened a panel of European experts for this Position Statement. On December 18, 2024, panel members voted on their preferred recommendation between two choices about CADe during colonoscopy for indications of CRC screening or polyp surveillance. Out of 19 eligible votes, 13 (68.4%) voted to recommend CADe for colonoscopy, and six panel members (31.6%) voted against. Therefore, the current ESGE statement is:RecommendationThe panel believes that most well-informed patients who have already decided to undergo colonoscopy for screening or surveillance would favor CADe assistance during colonoscopy. This is due to the potential benefits, although limited, of reduction in colorectal cancer incidence and mortality.This recommendation is weak, because the evidence is limited with considerable uncertainty of the evidence estimates, the absolute benefits for colorectal cancer incidence and mortality are small, and there is a patient burden associated with CADe (more polyp overdiagnosis and more colonoscopy surveillance).